Hematopoietic Effects of Chemotherapy in Pediatric Patients with Acute Lymphoblastic Leukemia: A Systematic Review - Primartati, Danny Meganingdyah; Fatmariza, Aulia Risqi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: Chemotherapy is the mainstay of treatment for pediatric acute lymphoblastic leukemia (ALL) but is frequently associated with significant hematopoietic suppression. This systematic review aimed to evaluate the effects of chemotherapy on hematopoietic suppression and recovery in pediatric patients with acute lymphoblastic leukemia. Methods: This systematic review was registered in PROSPERO (CRD420251074627) and conducted according to PRISMA 2020 guidelines. Literature searches were performed in PubMed, ScienceDirect, and SpringerLink for studies published between 2020 and 2025. Original studies assessing chemotherapy-related hematopoietic changes in pediatric ALL were included. After screening titles, abstracts, and full texts, 7 studies were eligible and synthesized narratively. Results: Induction chemotherapy consistently caused profound suppression of erythropoiesis, granulopoiesis, and thrombopoiesis, reflected by declines in hemoglobin, absolute neutrophil counts, and platelet counts. Hematopoietic recovery was phase-specific and lineage-dependent, with earlier erythroid recovery compared with neutrophil and platelet recovery. Early markers, including reticulocyte indices and immature platelet fraction, demonstrated earlier recovery than conventional blood counts. Bone marrow assessments showed delayed restoration of marrow cellularity and hematopoietic stem cell compartments despite morphologic remission. Conclusion: Chemotherapy-induced hematopoietic suppression in pediatric ALL is marked and heterogeneous, with recovery extending beyond morphologic remission. Integrated monitoring using peripheral blood parameters, early recovery markers, and selective bone marrow evaluation may improve assessment of hematopoietic recovery and supportive care during treatment